Support Group for Patients with Cardiovascular Diseases and How to Build Intimation Within Them: A Literature Review - Cahyati, Ai; Nurachmah, Elly; Masfuri, Masfuri; Siregar, Kemal N. (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Cardiovascular disease (CVD) is a deadly disease and patients need to adhere to a self-care management program for the rest of their lives. Many patients fail to maintain their condition and require re-hospitalization which is assumed due to lack of support. Support groups are a continuity of care effort for patients with cardiovascular disease that are useful as a place for sharing, education, and recreation. This paper aims to gather information and analyze evidence-based information regarding the role of support groups for cardiovascular patients and how to build intimacy in these support groups. The method is based on a literature review of relevant databases surrounding intimacy in support groups for patients with cardiovascular disease. The results of the study showed that support group activities can be organized by peer groups or professional groups which are carried out online or offline. The success of a support group as a medium for changing patient behavior depends on the intimacy/closeness that is formed within the group itself. The intimacy that can be seen from members feeling the need for a support group is the potential for support group activities to last a long time. A support group with a climate of intimacy has been formed to provide continuity of care for cardiovascular disease patients. Support groups that have established intimacy between group members are very necessary for patients with CVD to increase compliance and prevent readmission. Keywords: Support Group; Intimacy; Cardiovascular Disease